EVALUASI DEWAN PENGAWAS SYARIAH TERHADAP PENGUNGKAPAN LAPORAN DANA ZAKAT PADA BANK UMUM SYARIAH DI INDONESIA - Sayu Mainingsih (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The zakat fund report is one of the main components of financial statements that must be presented by Islamic bank entities. This is one of management responsibility as an annual report. One of the main sources for gaining public trust is the level of quality of information provided to the public. Islamic banking must convince the publics that all activities carried out in accordance with Islamic sharia. In the Statement of The Financial Accounting Standards (PSAK) number 101, there are still mismatches in the disclosure report of zakat funds, the distribution of zakat funds where there is less transparency in the distribution of alms funds to 8 asnafs ( parties that are eligible to receive Zakat collected from Muslims) which has become the obligation of zakat recipients. Instead of that, the role of DPS is as a spiritual role in sharia banking, in this case DPS is also a differentiator between Islamic banks and conventional banks. Keywords: Sharia Supervisory Board, Zakat fund report, PSAK No.101